Duodenal inhibition of gastric secretion by osmotic agents in normal subjects and patients with duodenal ulcer. Issue 12 (December 1969) - Ward, A. S.; Wilkins, R. A.; Cockel, R.; Windsor, C. W. O.
Abstract : Gastric secretion in man is inhibited by the presence in the duodenum of hyperosmolar and hypoosmolar solutions. Both acid and pepsin outputs are affected. There is no change in hydrogen, sodium, or potassium ion concentration in the gastric juice. Pepsin concentration, however, is reduced by all inhibitory stimuli. Inhibition is thought to act directly upon parietal and chief cells, and a possible basis for this mechanism is discussed. The response is similar in control subjects and duodenal ulcer patients; there is in particular no evidence of impaired inhibition in the ulcer group. An anomalous feature is the relatively small inhibition of acid output after hypertonic saline in control subjects compared with the duodenal ulcer patients.